Establishing Priorities for Urban Green Infrastructure Research in Australia. Issue 1 (2nd January 2019) - Lin, Brenda B.; Meyers, Jacqui A.; Barnett, Guy B.
ABSTRACT: Green infrastructure (GI) is a vital asset for sustainable cities, but an interdisciplinary approach must be taken if multifunctional and socially acceptable GI is to be developed. Here, we present the results of a workshop process to connect researchers and practitioners across academia, industry, and government and to enable a multidisciplinary group of participants to coalesce on a set of cross-cutting issues and prioritise a research agenda to address and advance GI research and uptake in Australia. We found that many of the challenges were ubiquitous across regions and scales, but research in a few key priority areas could advance GI across multiple cities. The key research areas were: Attitudes & Perceptions of GI; Increasing Biodiversity through GI; Optimising Spatial Configuration and Composition for Multiple Benefits; Economic Valuation of GI; Metrics, Models and Tools for Benchmarking Assessments; and Turning Research into Policy and Implementation. Although participants saw that there were many synergies across the research topics, there were challenges of translating the science for decision making and of establishing long-term institutional collaborations. However, urgency for sound evidence to support policy development and planning will require an interdisciplinary process to be maintained so that clear communication can be established across sectors.